ANGOLAN TRAITS IN BLACK MUSIC, GAMES AND DANCES OF BRAZIL, A study of African cultural extensions overseas, by Gerhard Kubik, Junta de Investigacoes Cientificas do Ultramar, Centro de Estudos de Antropologia Cultural, No. 10, Lisbon, 1979. pp 55, photographs. - De Oliveira Pinto, Tiago (International Library of African Music, 1987)
pages: 155-159
Keywords: Music; African Music; Angola; Brazil; Black Music